Analysis of four periapical inflammatory lesions findings on periapical radiographs: a case report - Muchlis, Muhammad Rakhmat Ersyad; Arsyad, M Aksa; Annisa, Nabila Ainun (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2025)
Objectives: To analyze four periapical inflammatory lesions on periapical radiographs. Case Report: A 20-year-old male patient came to RSIGMP-UMI, the results of the intraoral clinic examination showed that there was a crown restoration in the area of 13 to 23 that the patient had been using since ± 5 years ago. Discussion: Radiographs are a necessary supporting examination, especially after anamnesis and clinical examination for lesions involving bone tissue and its surrounding structure, periapical inflammatory lesions are the most commonly found pathological condition, defined as the local response of the bone around the dental apical. Conclusion: Periapical radiographic examination is very helpful in determining the exact diagnosis and treatment plan as well as evaluating the treatment results of a case, especially in cases of periapical inflammatory lesions.